Diseño y simulación de un molino compacto con transmisión interna para granos secos y cargue automatizado del producto - Meza Montes, Alberto Raúl; Vargas Nascimento, Cristian (Universidad Antonio Nariño, 2021)
The main objective of this project is to design and simulate a compact friction disk mill with internal transmission for the processing of dry grains, through automated processes, with the capacity to grind three hundred kilograms per hour. The purpose is to contribute to the improvement of the final product, the production times and the least possible human force intervention used in the conventional methods for this activity. With the application of the proposed prototype, small and medium-sized companies dedicated to the milling of dry grains will be favored, they can be an improvement in their production line and increase their competitiveness, in addition to guaranteeing the well-being of their users. It is a technological development, given that it seeks to provide an immediate or short-term solution to a problematic situation. A simulation is performed in the Solid Edge CAD software of the design made observing the operation of its parts together so it can also be framed in an experimental investigation. The calculations developed and the selection methods used to achieve the proposed objectives were carried out on the most important mechanical and electrical elements used in prototypes of disk mills and automatic machines, as the dimensions of the endless screws, geared motors, grinding discs, bearings, and all the elements that are necessary for this prototype to be an option that contains a high capacity and quality in the processing of dry grains.